2008
DOI: 10.1529/biophysj.107.117606
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Molecular Dynamics Evidence for a Sequential Mechanism for the A-to-B Transition in DNA

Abstract: The A-to-B form transition has been examined in three DNA duplexes, d(CGCGAATTCGCG)(2), d(CGCGAATTGCGC), and d(CGCAAATTTCGC), using circular dichroism spectroscopy, ultraviolet resonance Raman (UVRR) spectroscopy, and molecular dynamics (MD) simulation. Circular dichroism spectra confirm that these molecules adopt the A form under conditions of reduced water activity. UVRR results, obtained under similar conditions, suggest that the transition involves a series of intermediate forms between A and B. Cooperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 84 publications
5
51
1
Order By: Relevance
“…14 The effect of intrinsic sequence is considered as one of the most important factors on keeping DNA conformation. [15][16][17][18] Recently, Lavery et al 19 described 39 different DNA oligomers in explicit solvent and showed that sequence-effects increased at the tri-or tetranucleotide level, whereas dinucleotide models were insufficient for predicting sequence-dependent behavior. In physiological conditions, DNA conformation keeps a very delicate balance of many kinds of interactions: base stacking, backbones, hydrogen-bonds, solvent environment, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The effect of intrinsic sequence is considered as one of the most important factors on keeping DNA conformation. [15][16][17][18] Recently, Lavery et al 19 described 39 different DNA oligomers in explicit solvent and showed that sequence-effects increased at the tri-or tetranucleotide level, whereas dinucleotide models were insufficient for predicting sequence-dependent behavior. In physiological conditions, DNA conformation keeps a very delicate balance of many kinds of interactions: base stacking, backbones, hydrogen-bonds, solvent environment, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In physiological conditions, DNA conformation keeps a very delicate balance of many kinds of interactions: base stacking, backbones, hydrogen-bonds, solvent environment, etc. [20][21][22][23][24][25] Oostenbrink and van Gunsteren 26 calculated different free energy of base pairing and base stacking. Through the analysis of a diverse set of 23 natural and unnatural bases, they found stacking free energies and stacking conformations were crucial in pairing of DNA nucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…UV resonance Raman wavenumbers (cm À1 ) and tentative assignments of LacDNA complexes in different physico-chemical conditions, of the corresponding single-stranded oligonucleotides and of the proper sum of spectra of single oligonucleotides. [1,5,11,19,20,[23][24][25][26][27][28][29][30][31][32] Raman spectra were excited with a 275 nm laser line. The spectral resolution was appreciated to be 3 cm Intensity changes can also give insight into changes in coupling or electronic structure.…”
Section: Resultsmentioning
confidence: 99%
“…Wavenumber positions of the major peaks are presented in Figs 3 and 4, respectively, being in accordance with those given previously in the literature. [1,5,11,19,20,[23][24][25][26][27][28][29][30][31][32] Table 1 presents a detailed comparative analysis of the UV (275 nm) resonance Raman markers of the six LacDNA complexes, the corresponding single-stranded oligonucleotides (SS1 and SS2) and the proper sum of spectra of single oligonucleotides. Proposed UVRR band assignments found in the literature for similar compounds are also included.…”
Section: Uvrr Spectroscopymentioning
confidence: 99%
“…2(b), inset). Although DNA dimension along the duplex axis in the wet and dried states is slightly different [19][20][21], the TEM image of the inner surfaceto-surface distance between dimeric nanoparticles shows the relatively constant value of particle distance that may be due to the orientation of the DNA molecules. In the system studied, the DNA nanostructure was located between the Au nanoparticles in a direction perpendicular to the duplex axis, whereas in ordinary systems, they are usually aligned parallel.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%